Analisis Studi Literatur Kemampuan Berpikir Komputasi Menggunakan Software Matematika di SMA - Mustika Nurbayeni; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In the era of increasing digitalization, the integration of technology in education is becoming increasingly important. One area that has received a major contribution from technology is mathematics education at the secondary school (SMA) level. The use of mathematics software has become a highly effective tool for teachers and students in understanding complex mathematical concepts, developing computational skills, and solving problems more efficiently and interactively. This article analyzes various literature studies related to the use of mathematics software in high school, with a focus on developing students' computational thinking abilities. Computational thinking (CT) abilities, which were first introduced by Seymour Papert, are important skills that help students in decision making and problem solving. Various studies show that the integration of CT in educational curricula, particularly through teaching programming and the use of mathematical software, can improve students' computing skills. Although there are challenges in implementation, such as lack of infrastructure and teacher training, this study highlights the importance of using technology in mathematics education to create a dynamic, interactive, and relevant learning environment. This research aims to provide a comprehensive analysis of literature studies related to the use of mathematics software in high school and its influence on the development of students' computational thinking skills. By understanding the findings from previous studies, it is hoped that this research can make a significant contribution to designing a more effective mathematics curriculum and provide practical guidance for educators in integrating mathematics software in everyday learning. The results of the analysis show that technology-based interactive learning methods, the use of special software such as Matlab and Geogebra, as well as programming training with languages ​​such as Java and Python, all show positive results in improving students' computing skills. However, there is still a need to improve abstract thinking skills and address variations in computational abilities among students.